Immersive and Experiential Learning: A Review of Project-based Learning and Virtual Reality in Chemistry Education - Joronavalona, Rasamimanana; Rohaeti, Eli; Laksono, Endang Widjajanti; Anjamampionona Notiavina, Andriandrainiarimanana (Jurnal Pendidikan Matematika dan Sains, 2025)
This review explores the integration of Project-based Learning (PjBL) and Virtual/Augmented Reality (VR/AR) in chemistry education. By synthesizing findings from eight peer-reviewed studies published between 2020 and 2025, selected through a systematic search using the Dimensions.ai database with specific inclusion criteria, the review highlights how immersive technologies enhance conceptual understanding, motivation, and engagement in student-centered learning environments. Data were collected using a structured literature search, and the findings were analyzed through thematic synthesis based on educational level, technology used, implementation strategies, and reported outcomes. The review reveals that VR/AR, when effectively embedded in PjBL frameworks, allows learners to simulate experiments, visualize abstract molecular structures, and collaborate in meaningful, inquiry-driven projects. However, challenges remain, including limited access to technology, pedagogical integration issues, and educator resistance. The review concludes with recommendations for future research, emphasizing the need for teacher training, inclusive design, and long-term evaluation of immersive PjBL in chemistry education.